2018
DOI: 10.1111/rec.12678
|View full text |Cite
|
Sign up to set email alerts
|

GLMM BACI environmental impact analysis shows coastal dune restoration reduces seed predation on an endangered plant

Abstract: Invasive plants create refuge habitat for predators that results in increased levels of seed predation on native plants. We test the effects of a large-scale removal of the invasive plant Ammophila arenaria on the predispersal seed predation rate experienced by an endangered plant in a coastal dune ecosystem. Restoration resulted in a large and lasting reduction in seed predation in this system, and reducing predation could be an explicit goal in future restoration projects. The generalized linear mixed statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…[1,[8][9][10]. Globally this has led to substantial increases in dune fixation (stabilization) and a significant loss of naturally mobile (shifting) dunes [11][12][13][14][15][16]. Restoration strategies for coastal dune systems are complex because sandy dunes are exposed to multiple dynamic processes that operate on different temporal and spatial scales [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,[8][9][10]. Globally this has led to substantial increases in dune fixation (stabilization) and a significant loss of naturally mobile (shifting) dunes [11][12][13][14][15][16]. Restoration strategies for coastal dune systems are complex because sandy dunes are exposed to multiple dynamic processes that operate on different temporal and spatial scales [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Flora and fauna found on mobile dunes are often psammophilic, endemic species, highly adapted to harsh, xeric sandy conditions, and often form unique assemblages [6,[26][27][28][29][30][31]. Several researchers recognize that dune fixation, whether through succession or intentional re-establishment, can result in adverse consequences for mobile dune species [14,24,25,32,33]. In fact, a review of coastal management actions reported that dune fixation always had a negative impact on coastal species diversity, either through species loss or increase (e.g., invasive species), or changes in composition [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was infeasible to anticipate or enforce sampling quotas across commodities, locations, and time points. Our use of GLMM, a method well-suited to model unbalanced data ( Pardini et al, 2018 ; Pinheiro & Bates, 2001 ), enabled sound inferences to be made despite sampling constraints. Another limitation of this study is that it represents only a single year of observations.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing an adequate control treatment is necessary to perform Before‐After‐Control‐Impact analyses (i.e. BACI, BACIPS, or RCT study designs; Thiault et al 2017; Pardini et al 2018; Chevalier et al 2019). There was no reference ecosystem on Bagaud Island that was adequate for the duration of the study.…”
Section: Discussionmentioning
confidence: 99%